Surgical Management of Large Odontogenic Cysts of the Mandible. Issue 7 (October 2019) - Bonavolontà, Paola; Dell'Aversana Orabona, Giovanni; Friscia, Marco; Sani, Lorenzo; Abbate, Vincenzo; Iaconetta, Giorgio; Califano, Luigi
Abstract : Introduction: Odontogenic cysts are defined as those cysts that arise from odontogenic epithelium and occur in the tooth-bearing regions of the jaws. Cystectomy, marsupialization, or decompression of odontogenic cyst are the most common treatments proposed for this pathology. The aim of this study is to retrospectively evaluate the result of decompression based on the volumetric reduction of the cystic cavity and new bone formation by cone beam computerized tomography (CBCT). Methods: The 16 patients affected by a large odontogenic mandibular cyst were enrolled in the study. All the patients underwent a surgical decompression of the cyst followed by the enucleation after a follow-up ranging from 6 to 9 months according to the volume's reduction and new bone formation. All the patients were evaluated with a CBCT before and after the surgical decompression to measure and analyze the percentage of reduction of the cystic volume before proceeding with the enucleation. Results: The decompression of the cyst showed a reduction of the cystic volume ranging from 38.2% to 54.4% proportionally to the treatment duration. The highest percentage of volume reduction observed was 54.4% in 1 patient followed-up for 9 months, before the surgical enucleation. Conclusion: In our experience, the decompression seems to be the most suitable technique for the primary treatment of large odontogenic cyst of the jaws followed by the enucleation after 6 to 9 months. The CBCT is an objective method to evaluate the cystic volume reduction after the decompression and helps the surgeon with the surgical planning. Abstract : Supplemental Digital Content is available in the text